ACUTE EFFECTS OF BILATERAL AND UNILATERAL WHOLE BODY VIBRATION TRAINING ON JUMPING ABILITY, ASYMMETRY, AND BILATERAL DEFICIT ON FORMER ARTISTIC GYMNASTS - George Dallas; Vasiliki Kolovou; Panagiotis Pappas; Vasilis Mellos; Giorgos Paradisis (University of Ljubljana Press (Založba Univerze v Ljubljani), 2022)
Whole-body vibration (WBV) has been used to improve jumping ability, muscle strength, power, and performance in various sports. Bilateral deficit (BLD) is defined as the difference in the magnitude of the maximum force during single or double support. The present study investigated the effect of unilateral and bilateral whole-body vibration (WBV) exercise on jumping ability, asymmetry and BLD on former artistic gymnasts. Twenty-eight former artistic gymnasts volunteered to participate in this study. Participants performed 4 experimental protocols on nonconsecutive days in a random order. Each protocol included a 3-min-warm-up running on the treadmill at 2.22 m.s -1, followed by a 2-min rest. The intervention protocols were: a) WBV with feet [bipedal] (WBVB), b) WBV with single foot [unilateral] (WBVU), c) WBVB with the device turn-off (NWBVB), and d) WBVU with the device turn-off (NWBVU). The dependent variables were the squat jump (SJ) and counter movement jump (CMJ) with both feet (bilateral) and with single leg (unilateral). Results showed a significant interaction effect between the condition and time on SJ on both condition (bilateral and unilateral) and CMJ, whereas significant main effect was found for the condition and for time on SJ. Conclusively, the WBV unilateral condition improves significantly lower limbs symmetry during SJ performance. Further, bilateral WBV (WBV B) was the most effective condition on bilateral and unilateral SJ and CMJ performance.